Radio-frequency characterization of multi-walled carbon nanotube/poly-lactic acid composites - Sukgorn, Nuttaya; Siraleartmukul, Krisana; Yordsri, Visittapong; Chudpooti, Nonchanutt; Chaimool, Sarawuth; Akkaraekthalin, Prayoot; Chalermwisutkul, Suramate; Thanachayanont, Chanchana; Wongwiriyapan, Winadda; Chalapat, Khattiya (My University, 2017)
Nowadays radio and microwave frequencies are widely used in wireless broadcastings and communications. But these waves can cause electromagnetic interferences in some electronic devices, including the equipment used in hospitals. The problems of the electromagnetic interference can be solved by using the materials that can reflect and/or absorb radio-frequency (RF) and microwaves. The shielding effectiveness (SE) of a material depends on its conductivity and the electrical permittivity. Recently, carbon nanotubes (CNTs) have been proposed as promising materials for shielding applications owing to its flexibility, durability, lightweight and exceptional electrical conductivity compared to conventional metal. In this work, the RF properties of multi-walled carbon nanotube (MWCNT) composites were investigated. Poly-lactic acid (PLA), a natural bio-degradable material, is used as the polymer matrix. The composites with different MWCNT concentrations (0 to 0.4 wt%) were prepared and molded into thin rectangular samples (5.6 cm x 6.3cm). The surfaces of the composites were morphologically characterized by a scanning electron microscope. The electrical permittivity of the samples was measured by using a vector network analyzer and a microstrip resonator within a range of 1-11 GHz. The effects of MWCNT concentration on electrical permittivity will be discussed.
Keywords: Carbon Nanotube; Electrical Permittivity; Poly-Lactic Acid; Radio-Frequency Characterization